2021
DOI: 10.3390/polym13111890
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneimine-Oleic Acid Micelles-Stabilized Palladium Nanoparticles as Highly Efficient Catalyst to Treat Pollutants with Enhanced Performance

Abstract: Water soluble organic molecular pollution endangers human life and health. It becomes necessary to develop highly stable noble metal nanoparticles without aggregation in solution to improve their catalytic performance in treating pollution. Polyethyleneimine (PEI)-based stable micelles have the potential to stabilize noble metal nanoparticles due to the positive charge of PEI. In this study, we synthesized the amphiphilic PEI-oleic acid molecule by acylation reaction. Amphiphilic PEI-oleic acid assembled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Monoclonal antibodies that recognize tumor-associated antigens are perhaps the most extensively explored ligands for targeted drug delivery [57]. The exquisite specificity of antibodies makes them well suited for directing nanoparticles to cancer cells that are overexpressing cognate receptors [58].…”
Section: Targeting Ligandsmentioning
confidence: 99%
“…Monoclonal antibodies that recognize tumor-associated antigens are perhaps the most extensively explored ligands for targeted drug delivery [57]. The exquisite specificity of antibodies makes them well suited for directing nanoparticles to cancer cells that are overexpressing cognate receptors [58].…”
Section: Targeting Ligandsmentioning
confidence: 99%
“…PEI is a hydrophilic polymer analogue of PEG, with nitrogen atoms instead of oxygen, and its copolymers have been exploited for including metal ion absorption, in vivo imaging, targeted delivery of drugs, antibacterial, antifouling, and gene-transfection . Although a number of amphiphilic PEI-dominant copolymers are reported which contain hydrophobic segments, such as alkyl groups, poly­(ε-caprolactone) (PCL), tocopherol hydrogen succinate (TOS), oleic acid, and stearic acid, none of these are known to form thermogels in water. Replacement of PEG with PEI as the hydrophilic segment in thermogelling polymers can bring about several unique properties: on top of allowing convenient postsynthetic functionalization using well-established amine chemistry, the basic nitrogen atoms, with their propensity for protonation, also offer opportunities for pH-responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, amphiphilic polyethyleneimine (PEI)-oleic acid micelles-stabilized palladium nanoparticles were synthesized by Wang et al, which effectively catalyzed the reduction of 4-NP to form 4-AP and had high catalytic efficiency against morin. The authors concluded that these nanoparticles have great potential applications in treating various organic contaminants in solution in the future [ 14 ].…”
mentioning
confidence: 99%